(untitled) (Bangladesh Critical Care Journal, 2026)
Background: There is limited data on the etiological pattern of pleural effusion in diabetic patients. Therefore, it is imperative to understand the cause of pleural effusion in diabetic patients so that it may help in adoption of regionally optimized diagnostic & therapeutic approach. Methodology: This was a hospital based cross-sectional study carried out in the Department of Internal Medicine and Respiratory Medicine of BIRDEM General Hospital, Dhaka, Bangladesh over a duration of 6 months. All hospitalized adult (≥18 years) type 2 diabetic patients of either sex with exudative pleural effusion were included in the study. Pregnant women, non diabetic patients, patients with other forms of diabetes, bleeding disorders, chest trauma and non-aspirable pleural effusion were excluded. Investigations were done to find out the etiology of pleural effusion. Results: The mean age was found 57.9±16.7 years, ranging from 19 to 91 years. Almost three-fourth (72.0%) patients were male. Male to female ratio was 2.7:1. Forty four patients had tubercular pleural effusion, among them 27 (61.4%) were right sided and 17 (38.6%) were left sided pleural effusion. Thirty patients had pneumonia, among them 19 (63.3%) were right sided and 11 (36.7%) were left sided pleural effusion. Twenty six patients had malignancy, among them 15 (57.7%) were right sided and 11 (42.3%) were left sided pleural effusion. Causes of malignant pleural effusion were adenocarcinoma (42.3%), squamous cell carcinoma (26.7%), small cell carcinoma (19.2%), lymphoma (7.7%) and mesothelioma (3.8%). Conclusion: The most common cause of exudative pleural effusion in type 2 diabetic patients was tubercular pleural effusion. Bangladesh Crit Care J March 2026; 14 (1): 23-27